2001
DOI: 10.2134/jeq2001.3031040x
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on Cadmium Transport in Undisturbed Contaminated Sandy Soil Columns

Abstract: Limited information is available on the effects of contaminant aging (i.e., the contact time of Cd with the soil) on Cd transport in soils. We conducted displacement experiments in which indigenous Cd and freshly applied Cd were leached simultaneously from undisturbed samples of three Spodosol horizons. Sorption of Cd was described using Freundlich isotherms, whereas transport was described as a convection-dispersion process. Parameter optimization analysis using a mobile-immobile transport model applied to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…The results with respect to Pb transport and sorption are less conclusive. The mass transfer coefficient points to a nonequilibrium process (ω b 1), but the value of β reveals that a larger amount of these cations are sorbed at equilibrium sites than at nonequilibrium sites (Candela et al, 2007;Seuntjens et al, 2001;van Genuchten, 1981). According to the batch experiment results, both Cr and Pb cations were retained at sites with high sorption energies; therefore, sorption at nonequilibrium sites seems to be predominant, as this reaction is kinetically controlled.…”
Section: Flow Experimentsmentioning
confidence: 99%
“…The results with respect to Pb transport and sorption are less conclusive. The mass transfer coefficient points to a nonequilibrium process (ω b 1), but the value of β reveals that a larger amount of these cations are sorbed at equilibrium sites than at nonequilibrium sites (Candela et al, 2007;Seuntjens et al, 2001;van Genuchten, 1981). According to the batch experiment results, both Cr and Pb cations were retained at sites with high sorption energies; therefore, sorption at nonequilibrium sites seems to be predominant, as this reaction is kinetically controlled.…”
Section: Flow Experimentsmentioning
confidence: 99%
“…In the mean time, the "ageing effects" of ion adsorption to clay minerals will also take place, which has generally been attributed to micropore diffusion, cavity entrapment, occlusion in solid phases by coprecipitation and co-flocculation, and surface precipitation/crystal growth (Alexander, 2000;Seuntjens et al, 2001;Ma et al, 2006). With ageing, metal is generally subject to transformation or incorporation into a more stable solid phase that can lead to a decrease in metal bioavailability.…”
Section: Effects Of Incubation Time On Free and Soluble Metal Ion Conmentioning
confidence: 99%
“…The latter explanation is more plausible. Seuntjens et al (2001) reported that solutes can migrate into less accessible soil regions and become strongly bound over time. Except soil A, from which 8.02 mg Zn per column were eluted in the unamended treatment (Table 2), in the other soils total amounts of eluted Zn were never higher than 35% of the added (i.e., 3.41 mg per column in the unamended treatment in soil G).…”
Section: Zinc Breakthroughmentioning
confidence: 99%